DAMPAK PANDEMI TERHADAP PEREKONOMIAN PEDAGANG KECIL DI KOTA TANJUNGPINANG - maria innest (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2022)
Covid-19 is a pandemic that is currently ravaging Indonesia and brings a lot of changes to economic and social aspects. The majority of the population in the Tanjungpinang that trade with the percentage of 80,19%. As the driving force of the economic growth, the sector is the source for revenue if managed properly. This problem motivated the authors to explore how the impact of Covid-19 to the small traders. This research aims to explore about effect of the pandemic Covid-19 against to the small traders in Tanjungpinang. This study uses secondary data from interviews and observation to the small traders. Testing using qualitative descriptive methods. The results of this research it can be concluded that when the pandemic Covid-19, bringing the influence of the small traders in Tanjungpinang , where in the time of pandemic, the small traders experienced a decline in income, and also a decrease in customers. But, pandemic is not brought the influence of the extreme to the economy of the household. To tackle this problem is small trader keep selling as always with a fixed implement with using mask, continue to comply with health protocols and reduce the stock of merchandise to avoid greater losses.